Comparison of the Reaction Time Period of Individuals in Sport, Fine Arts and Classroom Education - TEMUR, H. Bayram; BAYTAR, Rezan (Asian Journal of Education and Training, 2019)
In this study, it was aimed to compare the reaction times of individuals who are generally trained as sports teachers, fine arts teachers and class teachers, and in particular the reaction times of individuals according to the branches they receive education. For this purpose, 132 individuals from different branches and classroom teachers at the School of Physical Education and Sports and Faculty of Fine Arts were included in the study. Reaction time measurements were performed with NEWTEST 1000 instrument. Data analysis One-way Anova and Independent t test and Descriptives program were used in SPSS program. As a result of the analysis, it was found that the visual and auditory mixed reaction times of both hands were different between the groups at p <0.01. It was found that there was a difference in right hand mixed reaction time between groups at p <0.05 level. In addition, it was found that there was a difference between right hand visual and right and left hand mixed reaction time values at the level of p <0.01 between those who had badminton training and those who had picture training. It was determined that left hand visual and right hand auditory reaction time values were significantly shorter (p <0.01) in football training subjects when compared to those who had picture training. As a result, it can be said that being a sports instructor positively affects visual, auditory and mixed reaction time and also the branches involved in the study affect the reaction time at different levels.